The Examining of Entrepreneurial Intention Among Students with Entrepreneurial Education and Individual Value: Mediation Role of Human Capital - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2022)
This study aims to examine the mediating role of human capital on the effect of entrepreneurial education and individual value on entrepreneurial intention. This research was conducted on students majoring in business at a university in Bali with a population of 7,246 people. A sample of 379 and data was collected using a questionnaire that returned as much as 279. Testing the research model using PLS-SEM with WarpPLS 7.0. The findings show that entrepreneurial education influence human capital, and individual value has an effect on human capital. Entrepreneurial education can influence entrepreneurial intention. Individuals could an effect on entrepreneurial intention, human capital can influence entrepreneurial intention. This study also found that human capital was able to partially mediate the influence of entrepreneurial education on entrepreneurial intention. Human capital was almost not able to mediate individual value on entrepreneurial intention. This study shows evidence of the importance of entrepreneurship education and individual value for creating competitive human capital in generating entrepreneurial intentions. These findings also provide an understanding of developing entrepreneurial intention models with an entrepreneurial education system and value strategies that shape the competitiveness of human capital.